A CRISPR-Cas12a-based universal rapid scrub typhus diagnostic method targeting 16S rRNA of Orientia tsutsugamushi. - Bum Ju Park; Sang Taek Heo; Misun Kim; Jeong Rae Yoo; Eun Jin Bae; Su Yeon Kang; Sunghoon Park; Kyeo Re Han; Keun Hwa Lee; Jae Myun Lee; Hyeyoung Lee; Yoon-Jae Song (PLoS Neglected Tropical Diseases)
Scrub typhus is caused by Orientia tsutsugamushi infection and occurs frequently in an area called the Tsutsugamushi Triangle. Currently, there is no vaccine for O. tsutsugamushi, and its infection is treated with antibiotics such as doxycycline. Scrub typhus responds to effective treatment, and early treatment shortens the course of the disease, reduces mortality, and accelerates recovery. Therefore, it is important to rapidly diagnose O. tsutsugamushi infection to ensure successful outcomes. Here, we developed a CRISPR-Cas12a-based diagnostic method targeting the bacterial 16S rRNA to detect O. tsutsugamushi infection of all known genotypes. To reduce the possibility of contamination and increase field applicability, we designed the one-pot assay system in addition to conventional two-pot assay system. Using this method, we successfully detected up to 100 copies of in vitro transcribed O. tsutsugamushi 16S rRNA within 1 hour under isothermal conditions. In blood samples from patients confirmed to be infected with O. tsutsugamushi by nested PCR, the developed method exhibited a clinical sensitivity of 98% and high specificity. These data demonstrate that the presented method is applicable for the rapid and universal diagnosis of scrub typhus to facilitate timely and appropriate treatment.